Evaluation of the level of serum Interleukins (IL-2, IL-4, IL-15 andIL-17) and its relationship with disease severity in patients with alopecia areata, - Özge Aşkın; Sera Nur Yücesoy; Erkam Coşkun; Burhan Engin; Server Serdaroğlu (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Alopecia areata (AA) is a hair disease that causes hair loss without scarring. The etiopathogenesis of AA has not been fully understood yet. Objective: To determine serum interleukin levels (IL-2, IL-4, IL-15, and IL-17) in patients diagnosed with alopecia areata and to investigate the relationship of IL levels with the duration and severity of alopecia areata and the response to tofacitinib therapy. Methods: Patients (≥16 years old) diagnosed with alopecia areata and healthy individuals as a control group was enrolled. Baseline serum interleukin levels of the patients and controls were measured. In the patient group receiving tofacitinib therapy, serum interleukin levels were measured again after 6 months. Disease severity for alopecia areata was assessed using the Severity of Alopecia Tool. Results: Sixty-one AA patients and 30 healthy individuals were included; they were comparable regarding age and sex. The mean disease duration for AA was 7 ± 6 years and the baseline mean Severity of Alopecia Tool score was 71 ± 30 (range, 20-100). Baseline IL-2, IL-4 and IL-15 levels were significantly higher in the patient group than those in the control group (p < 0.001 for each). No significant correlation was found between the baseline interleukin levels and either disease duration or disease severity (baseline Severity of Alopecia Tool score). Among the patients receiving tofacitinib (n = 22), all interleukin levels significantly decreased after treatment. However, no significant relationship between the change in interleukin levels and the change in the Severity of Alopecia Tool scores was observed after tofacitinib treatment. Study limitations: This is a monocentric study conducted in a single university hospital. Conclusion: High interleukin levels in alopecia areata patients and the significant decrease with treatment support the idea that interleukins have a role in pathogenesis. Nevertheless, no relationship could be demonstrated between IL levels and disease duration or severity.